Digital Storytelling Design: Riau Malay Folklore - Sri Yuliani; Andi Idayani; Widia Yunita; Yulianto Yulianto; Dicki Hartanto (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this research was to find out the effectiveness and practicality of the product of digital storytelling in the online English classroom. The researchers, previously, noticed that the varieties of media needed to be developed in maintaining Malay folklore. This research offers insights into the effectiveness and practicality of digital storytelling in preserving Malay folklore. This research is using a mixed-method quantitative and qualitative design. This research population was Islamic junior high school students in the first grade from three schools in Pekanbaru and eight pre-service English teachers involved in implementing the digital storytelling videos. The evaluation results showed that the design of digital storytelling videos showed the effectivity of digital storytelling products was high and practically on how digital storytelling videos were developed and applied in English class was also high. The implementation of digital storytelling videos was successfully done by the pre-service students and the appropriateness was high which can be used in the online English classroom.